Prebiotic property of tamarind seed kernel on Bifidobacterium animalis growth and biofilm formation - Roongrawee Wandee; Khaetthareeya Sutthanut; Jenjira Songsri; Natthida Weerapreeyakul; Theera Rittirod; Patcharaporn Tippayawat; Orawan Yangkruea; Siraphop Jakcharoenpornchai (Food Chemistry: X)
This research explored the prebiotic potential of tamarind seed kernel powder (RTS), focusing on yield, nutritional composition, physicochemical properties using ATR-FTIR spectroscopy and colorimetric methods, effects on Bifidobacterium animalis in promoting the growth and biofilm formation compared to inulin using bacterial enumeration and crystal violet staining techniques, and the biofilm biomolecular composition characterization. The multi-nutrient composition RTS yielded 65.65 % (w/w), which significantly exhibited prebiotic activity in a dose-dependent manner with effective concentrations at 2.5 and 5 % RTS, stimulated B. animalis growth (rate 22 % • h-1) and enhanced biofilm formation (BFI = 256.71) exceeding the inulin. Moreover, ATR-FTIR spectroscopy and PCA analysis revealed the RTS-induced alteration of the biofilm's biomolecular composition, with a notable increase in amide A and a decrease in carboxylic hydroxyl groups. The study highlights RTS as a promising prebiotic agent with the potential for improving gut health, with further validation in the in vivo models being advisable.